The Effect of Salinity on the Release of Copper (Cu), Lead (Pb) And Zinc (Zn) from Tailing - Apriani Sulu Parubak; Eko Sugiharto; Mudjiran Mudjiran (Indonesian Journal of Chemistry, 2001)
The effects of salinity on the release of copper (Cu), lead (Pb) and zinc (Zn) in tailing sediment have been studied by stripping voltammetry. The purpose of the research is to know the effect of salinity on the release of metals with certain pH, conductivity and variety of metals. Simultaneous determination of copper, lead and zinc in tailing was done by Differential Pulse Anodic Stripping Voltammetry (DPASV) onto hanging mercury drop electrode (HMDE) and nitric acid 65% as support electrolyte. The limit of detection for this method 0.60 µg/L, 0.150 µg/L and 0.238 µg/L for copper, lead and iMc respectively. The stripping solution of 300/00 salinity with pH= 7.85, conductivity= 46.62 mS/cm gives the amounts of released metals as follows :14.867 µg/L Cu, 0.976 µg/L Pb and 6.224 µg/L Zn. These results are higher as compared with the results from 15 0/00 salinity with pH= 7.66, conductivity= 23.22 mS/cm that give released metals of Cu= 7.988 µg/L, Pb= 0.311 µg/L and Zn= 4.699 µg/L. the results from ANOVA suggest that this is due to different in salinity of the solution. It also found that the conductivity does not give any effect. It can be concluded that the higher salinity will that give higher concentration or released metals.